2019
DOI: 10.1111/lam.13101
|View full text |Cite
|
Sign up to set email alerts
|

Effective biosynthesis of benzoyl-pyrrothine dithiolopyrrolone antibiotic by cinnamic acid-precursor addition in culture of Saccharothrix algeriensis NRRL B-24137

Abstract: Dithiolopyrrolone antibiotics, produced by several micro‐organisms, are known for their strong antimicrobial and antitumor activities. Among of this micro‐organisms, Saccharothrix algeriensis NRRL B‐24137, a rare actinobacterium, has the ability to produce several dithiolopyrrolones derivatives depending on precursors added in the culture medium. After 10 days of strain fermentation on semi‐synthetic medium supplemented with cinnamic acid and HPLC purification, biosynthesis of benzoyl‐pyrrothine dithiolopyrrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The new dithiolopyrrolone antibiotic PR11 showed moderate to strong activity against all Gram‐positive bacteria, filamentous fungi and yeasts tested, but no activity against Gram‐negative bacteria. Similar results were observed with other known dithiolopyrrolones produced by our strain (Lamari et al ; Merrouche et al , , ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The new dithiolopyrrolone antibiotic PR11 showed moderate to strong activity against all Gram‐positive bacteria, filamentous fungi and yeasts tested, but no activity against Gram‐negative bacteria. Similar results were observed with other known dithiolopyrrolones produced by our strain (Lamari et al ; Merrouche et al , , ).…”
Section: Resultssupporting
confidence: 93%
“…Our previous studies showed that the antibacterial and antifungal activities of the dithiolopyrrolones are related to their variable acyl groups (Merrouche et al , , ). The new dithiolopyrrolone antibiotic PR11 showed moderate to strong activity against all Gram‐positive bacteria, filamentous fungi and yeasts tested, but no activity against Gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the same authors have reported on the new benzoyl-pyrrothine dithiolopyrrolone (14), obtained after the supplementation of cinnamic acid into the culture medium of S. algeriensis NRRL B-24137. In the antibacterial evaluation, Listeria monocytogenes resulted in the most sensitive to the treatment with this pure metabolite (MIC = 4 µg/mL corresponding to 13.8 µM) [84].…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Compound 47 emerged as the most active in the series, mainly on Gram-positive bacteria and fungi (MICs in the range 1-50 µg/mL corresponding to 4.6-230 µM). [24,81] Valerylpyrrothine (6), Isovalerylpyrrothine (7), Formylpyrrothine (8), Aureothricin (9) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137, fully sequenced strain Saharan soil [82] Crotonyl-pyrrothine (10), Sorbyl-pyrrothine (11), 2-Hexenyl-pyrrothine (12), 2-Methyl-3-pentenyl-pyrrothine (13) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137 Saharan soil [83] Benzoyl-pyrrothine dithiolopyrrolone (14) antibacterial, antifungal Saccharothrix algeriensis NRRL B-24137 palm grove soil (Southern Algeria) [84] Mutactimycin PR (15) Toumatia et al [110] and, recently, Djinni et al [111] isolated novel strains producing actinomycin D (49) and showed that genus Streptomyces isolated from Saharan soil of Ain amenas (Streptomyces sp. IA1) and Beni Abbes-Bechar (Streptomyces sp.…”
Section: Antimicrobialsmentioning
confidence: 99%